Posterior reversible encephalopathy syndrome after postpartum hemorrhage and uterine artery embolization: A case report. Issue 49 (December 2017) - Shi, Fangfang; Shen, Liwei; Shi, Yonghui; Shi, Lei; Yang, Xiaoli; Jin, Zhi; Liu, Wenpeng; Wu, Danhong
Abstract: Rationale: Posterior reversible encephalopathy syndrome (PRES) is characterized by clinical and radiological features, including headache, disturbed consciousness, seizures, and cortical blindness associated with findings indicating posterior leukoencephalopathy on imaging studies. Ours is the first case of PRES developing after postpartum hemorrhage and uterine artery embolization. Patient concerns: An 18-year-old patient had postpartum hemorrhage after a normal delivery. She required uterine artery embolization to stop the bleeding; however, she developed PRES 2 hours after the surgery. Diagnoses: Brain computed tomography suggested subarachnoid hemorrhage or cerebral venous sinus thrombosis. However, findings on magnetic resonance imaging were highly indicative of PRES. Interventions: The patient received diazepam and midazolam to prevent seizures. Outcomes: Seizures were controlled on the first day. The patient's visual acuity returned to normal on the fourth day of admission. Thirteen days after admission, her neurological signs and symptoms were completely managed. Lessons: PRES may be related to postpartum hemorrhage, blood pressure fluctuation, inflammation, and contrast agents. Collectively, they cause a breakage in the blood–brain barrier and endothelial cell damage, eventually leading to PRES. We also found PRES had many features similar with contrast-induced encephalopathy.